2015
DOI: 10.1007/s12029-015-9709-0
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adiposity is a Risk Factor for Poor Prognosis in Colorectal Cancer Patients Receiving Adjuvant Chemotherapy

Abstract: This study shows that visceral obesity increases the likelihood of a poor prognosis in CRC patients receiving adjuvant chemotherapy thus underlying the value of lifestyle interventions to minimize visceral obesity in this patient cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
68
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 28 publications
2
68
1
Order By: Relevance
“…Another review concluded that the increase in adiposity was associated with an increase of CC-related mortality and decreased the disease-free survival of CC in women and RC in men [25]. Other papers suggested that increased VF was a significant predictor of worst disease-free survival in patients with resectable CRC [10] and reduced overall survival in CRC patients receiving adjuvant chemotherapy [16]. In contrast, other works demonstrated that patients with higher VF tended to have better overall-survival that non-visceral obesity patients [12] and a meta-analyses concluded that there was insufficient evidence to prove the presence of a strong link between adiposity and survival [26].…”
Section: Discussionmentioning
confidence: 99%
“…Another review concluded that the increase in adiposity was associated with an increase of CC-related mortality and decreased the disease-free survival of CC in women and RC in men [25]. Other papers suggested that increased VF was a significant predictor of worst disease-free survival in patients with resectable CRC [10] and reduced overall survival in CRC patients receiving adjuvant chemotherapy [16]. In contrast, other works demonstrated that patients with higher VF tended to have better overall-survival that non-visceral obesity patients [12] and a meta-analyses concluded that there was insufficient evidence to prove the presence of a strong link between adiposity and survival [26].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies (Kang et al, 2012;Lee, Murphy et al, 2015;Yamamoto et al, 2012) used previously established cut-off points to discriminate patients with abnormal VAT. Although median or quartiles have been used to stratify patients, cut-off points for VAT associated with clinical significance have not been defined.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Among the studies hereby reviewed, VAT cross-sectional area was the most commonly used index, measured in 14 studies (Gaujoux et al, 2012;Guiu et al, 2010;Kaneko et al, 2015;Kang et al, 2012;Kim, Chin, Hwang, & Jun, 2014;Ladoire et al, 2011;Lee, Jeong et al, 2015;Lee, Murphy et al, 2015;Nault et al, 2015;Naya et al, 2010;Pecorelli et al, 2016;Slaughter et al, 2014;Steffens et al, 2011;Yamamoto et al, 2012). The distance or thickness between kidney and abdominal wall musculature at the level of renal vein has been used as a proxy for quantifying VAT in seven studies (Balentine, Enriquez et al, 2010;Clark et al, 2013;Li et al, 2015;Mathur et al, 2011;Miller et al, 2012;Papoulas et al, 2015;Pausch et al, 2012), by virtue of measurement efficiency and convenience.…”
Section: Methodological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, depletion of skeletal muscle mass, termed “sarcopenia,” is widely reported to confer a poor prognosis for patients with tumors of the gastrointestinal (GI) tract, associated with an increased rate of postoperative complications2 and impaired response to chemotherapy 1. A smaller number of studies also have reported relationships between subcutaneous or visceral adiposity and outcomes for several tumor types, including esophageal,8 pancreatic,9 and colorectal cancers 10,11. The majority of these studies have used image analysis of computed tomography (CT) scans to measure parameters of body composition, and the accuracy of this technique is now widely accepted 12.…”
mentioning
confidence: 99%